ЖӘҲӘННИҢ ЖЕР-СУЎ РЕСУРСЛАРЫ ҲӘМ АЗЫҚ-АЎҚАТ МОЛШЫЛЫҒЫН ДҮЗИЎ МАШҚАЛАЛАРЫ (глобал экономика мысалында) - Пренов, А.Б.; Гаипова, Р.Т.; Умаров, Е.К. (FAN va JAMIYAT, 2016)
The article deals with the peculiarities of the placement of land and water resources of the world economy in the context of sustainable development of its reserves in separate continents and countries of the world for industrial purposes under the influence of intellectual innovation of states, with different levels of economic development.